Projections of Global Events on Art Environments and Museums in Türkiye (Post 1980s) - Yaşar Özrili (Yakın Dönem Türkiye Araştırmaları)
Since the 1980s, global events have taken place on Earth whose effects have lasted for many years and affected many cultures economically, philosophically, religiously, socially, and politically. Some mass events that developed since the 1980s have formed the agenda of the art and museum community. Social events are loaded with imaginary concepts for the arts and artists. The findings obtained from the analyzed subjects were selected from events that have made a great impact on the world and whose effects have lasted for many years. The arts and artists have tried to create social awareness by processing these events of great global importance. The aim of this article is to examine how art environments and museums in Türkiye were affected by global events after 1980, how the events were handled, and how this interaction was reflected in art production and exhibition. This study uses document analysis and the survey model, which are qualitative research methods. Some of the principles of museums and art environments involve contributing to creating social consciousness in the face of social conditions, movements, and contradictions of their own era; class relations and conflicts; and the religious, intellectual, economic, and political developments that result from these.